Pregnancy outcomes in women with congenitally corrected transposition of the great arteries - D. Yang; H. F. Zhang; Q. Liu; Y. N. Li; J. Zhang; T. Zheng (IMR Press, 2020)
The aim of this study was to define the pregnancy outcomes in women with congenitally corrected transposition of the great arteries (cc-TGA). The medical databases at Anzhen Hospital between January 2011 and March 2018 were retrospectively reviewed. Data of 12 pregnant women with cc-TGA were collected. One patient was lost at 35 weeks of gestation. There were 8 (72.7%) term births and 3 (27.3%) premature births. Of the 11 deliveries, 2 (18.2%) were vaginal and 9 (81.8%) were cesarean. The baseline New York Heart Association (NYHA) functional class was I - II in 11 patients, II - III in 7 patients, and III - IV in 5 patients in the third trimester (P = 0.037). In the third trimester, 6 (50%) patients became symptomatic and experienced heart function deterioration compared with asymptomatic patients (6 vs. 0, P = 0.002). In the third trimester, tricuspid regurgitation (TR) was identified in 11 patients: 2 with mild TR, 4 with moderate TR, and 5 with severe TR. Five symptomatic patients developed severe TR, in which the rate of TR was significantly higher than that of asymptomatic patients (5 vs. 0, P = 0.015). No difference was found in NYHA class between the third trimester and 1 week after delivery (P > 0.05). One patient died of ventricular fibrillation at 3 months postpartum. Successful pregnancy can be achieved by most women with cc-TGA. The deterioration of right ventricular function is common among pregnant women with cc-TGA, and severe TR is a high risk factor resulting in deterioration of the right ventricular function.